Проблематика взаимосвязанной электромеханической системы станка при скоростной металлообработке - Внуков, Юрий Николаевич; Пирожок, Андрей Владимирович (НТУ "ХПИ", 2013)
The analysis of causes of the regenerating vibration at intensive metal-cutting mode under the influence of vibration trace on transient surface was made. It was found its physical meaning, reasons and regularity. For suppression the self-vibration processes and improving quality at high-speed metal cutting it was introduced the usage of the adaptive speed control system for main drive spindle.
Problems of interdependent electromechanical mechine system for high-speed metal working
Keywords: металлообрабатывающие станки; обработка резанием; регенерация колебаний; система подавления автоколебаний; частота вращения шпинделя; девиация скорости резания